Specimen 2017 H2 Mathematics Paper 1 Question 8

Differentiation I: Tangents and Normals, Parametric Curves
Definite Integrals: Areas and Volumes

Answers

y=xtanp+asinp.{y = - x \tan p + a \sin p.}
Length AB=a.{AB = a.}
x23+y23=1.{x^{\frac{2}{3}} + y^{\frac{2}{3}} = 1.}
16105π units2.{\frac{16}{105}\pi \textrm{ units}^2.}

Full solutions

(a)

dydx=dydt÷dxdt=3acostsin2t3asintcos2t=sintcost=tant\begin{align*} \frac{\mathrm{d}y}{\mathrm{d}x} &= \frac{\mathrm{d}y}{\mathrm{d}t} \div \frac{\mathrm{d}x}{\mathrm{d}t} \\ &= \frac{3a \cos t \sin^2 t}{-3a \sin t \cos^2 t} \\ &= -\frac{\sin t}{\cos t} \\ &= -\tan t \end{align*}
At point P,{P,} equation of tangent:
yasin3p=(tanp)(xacos3p)y=xtanp+asinpcos2p+asin3py=xtanp+asinp(cos2p+sin2p)y=xtanp+asinp  \begin{gather*} y - a \sin^3 p = (-\tan p) (x - a\cos^3 p) \\ y = - x \tan p + a \sin p \cos^2 p + a \sin^3 p \\ y = - x \tan p + a \sin p (\cos^2 p + \sin^2 p) \\ y = - x \tan p + a \sin p \; \blacksquare \end{gather*}

(b)

At point B,x=0,{B, x=0,} y=asinp{y=a\sin p}

At point A,y=0,{A, y=0,}

0=xtanp+asinpx=asinptanpx=acosp\begin{gather*} 0 = -x \tan p + a \sin p \\ x = \frac{a \sin p}{\tan p} \\ x = a \cos p \end{gather*}
Length AB=(acosp)2+(asinp)2=a2(cos2p+sin2p)=awhich depends only on a  \begin{align*} & \textrm{Length } AB \\ & = \sqrt{(a\cos p)^2 + (a \sin p)^2} \\ & = \sqrt{a^2 (\cos^2 p+ \sin^2 p)} \\ & = a \\ & \textrm{which depends only on } a \; \blacksquare \end{align*}

(c)

cost=x13sint=y13\begin{align} && \quad \cos t &= x^{\frac{1}{3}} \\ && \quad \sin t &= y^{\frac{1}{3}} \\ \end{align}
Since cos2t+sin2t=1,{\cos^2 t + \sin^2 t = 1,} Cartesian equation of C:{C:}
x23+y23=1  x^{\frac{2}{3}} + y^{\frac{2}{3}} = 1 \; \blacksquare

(d)

Volume=π01x2  dy=π01(1y23)3  dy=π0113y23+3y43y2  dy=π[y95y53+97y7313y3]02=16105π units2  \begin{align*} & \textrm{Volume} \\ & = \pi \int_0^1 x^2 \; \mathrm{d}y \\ & = \pi \int_0^1 \left( 1-y^{\frac{2}{3}} \right)^3 \; \mathrm{d}y \\ & = \pi \int_0^1 1 - 3 y^{\frac{2}{3}} + 3 y^{\frac{4}{3}} - y^2 \; \mathrm{d}y \\ & = \pi \left[ y - \frac{9}{5} y^{\frac{5}{3}} + \frac{9}{7} y^{\frac{7}{3}} - \frac{1}{3} y^3 \right]_0^2 \\ & = \frac{16}{105} \pi \textrm{ units}^2 \; \blacksquare \end{align*}